Proceedings Design, Automation and Test in Europe Conference and Exhibition
DOI: 10.1109/date.2004.1268844
|View full text |Cite
|
Sign up to set email alerts
|

Automatic verification of safety and liveness for XScale-like processor models using WEB refinements

Abstract: We show how to automatically verify that a complex XScale-like pipelined machine model is a WEB-refinement of an instruction set architecture model, which implies that the machines satisfy the same safety and liveness properties. Automation is achieved by reducing the WEB-refinement proof obligation to a formula in the logic of Counter arithmetic with Lambda expressions and Uninterpreted functions (CLU). We use UCLID to transform the resulting CLU formula into a CNF formula, which is then checked with a SAT so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 20 publications
0
40
0
Order By: Relevance
“…For example, a big advantage over previous work is that we can handle liveness; in fact, we show that with our approach the time spent proving liveness accounts for only 5% of the total verification time [17].…”
Section: Automationmentioning
confidence: 86%
“…For example, a big advantage over previous work is that we can handle liveness; in fact, we show that with our approach the time spent proving liveness accounts for only 5% of the total verification time [17].…”
Section: Automationmentioning
confidence: 86%
“…5. Another approach suitable for proving both safety and liveness of pipelined processors was proposed in [24], but was not applied to designs with multicycle functional units.…”
Section: Related Workmentioning
confidence: 99%
“…In fact, BAT was able to solve the specification without calling the SAT solver by using the rewrite rules described in Section 4. Two Stage Pipelined Machine (2f ) Benchmarks: The 2f is a flushing based refinement theorem [14] for a simple 2 stage pipelined machine that implements only an add instruction and has two memory elements, which are the instruction memory and the register file as shown in Figure 5(a). We used the 2f benchmarks to compare BAT with VCEGAR, and found that VCEGAR cannot handle any of these benchmarks.…”
Section: Instruction Cache Ram (Icram) Unit (Icram) Benchmarksmentioning
confidence: 99%
“…We did not use VCEGAR to check the 5f and the 5fb benchmarks, as they are far more complex than the 2f benchmarks, which VCEGAR was not able to handle. Three Stage Pipelined Machine (3c) Benchmarks: The 3c benchmark is a commitment based refinement theorem [14] for a 3 stage pipeline, which has an instruction memory, a register file, and a data memory. Table 2 shows the BAT verification times for the 3c benchmarks obtained by increasing the number of words in the memory elements (N).…”
Section: Instruction Cache Ram (Icram) Unit (Icram) Benchmarksmentioning
confidence: 99%
See 1 more Smart Citation